Phase change material and memory

By doping phase change materials with Hf and In elements, the problem of poor adhesion between phase change materials and electrodes is solved, improving the performance stability and operating speed of the memory, expanding the storage window, reducing the risk of stripping, and promoting large-scale production.

CN119300703APending Publication Date: 2025-01-10SHENZHEN HONGQIXIN TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411243291.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing phase change materials have poor adhesion to electrodes and are prone to peeling, leading to unstable performance of memory chips and memory.

Method used

By doping Hf and In elements into phase change materials, a certain proportion of Hf and In doped matrix materials are formed, which improves the structural stability and adhesion of phase change materials and reduces the risk of peeling between the phase change layer and the electrode.

Benefits of technology

It improves the performance stability of memory chips and memory, enhances the operating speed, cycle endurance and memory window of memory, reduces production risks, and promotes large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119300703A_ABST
    Figure CN119300703A_ABST
Patent Text Reader

Abstract

The invention provides a phase change material and a memory. The phase change material comprises a base material, an Hf element and an In element. The atomic number percentage of the Hf element in the phase change material is greater than 0 and less than or equal to 20%. And the atomic number percentage of the In element in the phase change material is greater than 0 and less than or equal to 20%. The phase change material can reduce the risk that the phase change material is stripped from an electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of storage technology, and in particular to a phase change material and a memory. Background Art

[0002] In response to the limitation of von Neumann bottleneck on the improvement of computer system performance, the industry has proposed a storage-class memory (SCM) with a storage speed and capacity between dynamic random access memory (DRAM) and flash memory. Among them, phase change memory is one of the few storage-class memory alternatives that has been mass-produced. At present, sulfur compounds including Sb elements as phase change materials can enable memory chips to achieve high-speed operation. However, sulfur compounds including Sb elements usually have poor adhesion and easy peeling.

[0003] Therefore, a technical solution needs to be proposed to improve the problem that the phase change material has poor adhesion and is easy to peel off. Summary of the invention

[0004] The present application provides a phase change material and a memory to improve the problem of poor adhesion between the phase change material and an electrode and easy peeling.

[0005] In a first aspect, the present application provides a phase change material, the phase change material comprising:

[0006] Base material;

[0007] Hf element, the atomic number percentage of Hf element in the phase change material is greater than 0 and less than or equal to 20%; and

[0008] In element, the atomic number percentage of In element in the phase change material is greater than 0 and less than or equal to 20%.

[0009] In some embodiments, the atomic number percentage of the Hf element in the phase change material is greater than or equal to 1% and less than or equal to 15%;

[0010] The atomic number percentage of In element in the phase change material is greater than or equal to 1% and less than or equal to 18%.

[0011] In some embodiments, the phase change material further comprises:

[0012] Element A, element A is at least one element selected from C, N, O and Si, and the atomic number percentage of element A in the phase change material is greater than 0% and less than or equal to 20%.

[0013] In some embodiments, the atomic number percentage of the A element in the phase change material is greater than or equal to 1% and less than or equal to 10%.

[0014] In some embodiments, in the phase change material, the atomic number percentage of the In element in the phase change material is greater than the atomic number percentage of the A element in the phase change material.

[0015] In some embodiments, the matrix material includes at least one element of Ge, Sb, and Te.

[0016] In some embodiments, the matrix material includes Ge, Sb and Te;

[0017] In the phase change material, the atomic number percentage of Ge element is greater than or equal to 0% and less than or equal to 50%, the atomic number percentage of Sb element is greater than or equal to 10% and less than or equal to 50%, and the atomic number percentage of Te element is greater than or equal to 35% and less than or equal to 70%.

[0018] In some embodiments, the phase change material has the general chemical formula (N) x1 (Hf) y1 (In) z1 (Ge m1 Sb n1 Te k1 ) 1-x1-y1-z1 ;

[0019] Among them, x1 represents the atomic number percentage of N element, y1 represents the atomic number percentage of Hf element, z1 represents the atomic number percentage of In element, and m1 / n1 / k1 represents the atomic number ratio of Ge, Sb and Te; 0.1%≤x1≤10%, 0.1%≤y1≤10%, 0.1%≤z1≤20%, 0%≤m1≤50%, 10%≤n1≤50%, 35%≤k1≤70%.

[0020] In some embodiments, the phase change material includes (Ge 12.5 Sb 37.5 Te 50 ) 90 Hf5N4In1、(Ge 12.5 Sb 37.5 Te 50 ) 81 Hf5N4In 10 and (Ge 12.5 Sb 37.5 Te 50 ) 73 Hf5N4In 18 At least one of .

[0021] In a second aspect, the present application further provides a memory, which includes the phase change material of any of the above embodiments.

[0022] In the phase change material and memory provided in some embodiments of the present application, the phase change material includes a base material, an Hf element and an In element. The atomic percentage of the Hf element in the phase change material is greater than 0 and less than or equal to 20%. The atomic percentage of the In element in the phase change material is greater than 0 and less than or equal to 20%. In this way, a certain proportion of Hf elements and In elements are doped into the base material to jointly strengthen the atomic bonding strength in the phase change material and improve the structural stability of the phase change material. The risk of peeling between the phase change layer composed of the phase change material and the electrode is reduced, thereby improving the performance stability of the memory chip and the memory. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A block diagram of a memory according to some embodiments of the present application;

[0024] Figure 2 A schematic diagram of the structure of a memory chip in some embodiments provided in this application;

[0025] Figure 3 A schematic diagram of the structure of a memory chip according to some other embodiments of the present application;

[0026] Figure 4 A schematic diagram of the structure of a memory chip according to some other embodiments of the present application;

[0027] Figure 5 The test results of the SET speed and storage window of the memory of some embodiments and comparative examples of the application are shown in the figure; wherein, Figure 5 The line in R_RST represents the resistance value corresponding to the erase operation, the line in R_SET represents the resistance value corresponding to the write operation, the bar graph in R ratio represents the ratio of the resistance value corresponding to the erase operation to the resistance value corresponding to the write operation, and SET30ns to SET600ns represents the time of the write operation.

[0028] The reference numerals are as follows:

[0029] 300, memory; 100, storage chip; 200, controller;

[0030] 10. Storage unit;

[0031] 11, first memory cell; 111, first bottom electrode; 112, first selection layer; 113, first middle electrode; 114, first phase change layer; 115, first top electrode;

[0032] 12, second storage unit; 121, second bottom electrode; 122, second selection layer; 123, second middle electrode; 124, second phase change layer; 125, second top electrode;

[0033] 131, first bit line; 132, second bit line;

[0034] 141, first word line; 142, second word line;

[0035] z, first direction; x, second direction; y, third direction;

[0036] 21, substrate layer; 22, dielectric layer; 221, sink hole; 23, first electrode; 231, columnar contact portion; 232, lead portion; 24, second electrode; 25, phase change layer. DETAILED DESCRIPTION

[0037] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0038] Phase-Change Memory (PCM) is a type of memory that uses phase-change materials as storage media. The Joule heat generated by electrical pulses or light pulses is used to cause the phase-change material to undergo a reversible phase change between an amorphous state (the phase-change material is in a high-resistance state) and a crystalline state (the phase-change material is in a low-resistance state) to achieve data writing and erasing, and reading is achieved by measuring the size of the resistance.

[0039] Figure 1 The block diagram of the memory of some embodiments provided in the present application. The memory 300 includes a memory chip 100 and a controller 200, and the memory chip 100 is connected to the controller 200. The controller 200 is used to control the memory chip 100 to implement data writing, erasing and reading.

[0040] Figure 2 This is a schematic diagram of the structure of the memory chip of some embodiments provided in this application. Figure 2 As shown, the memory chip 100 may adopt a cross-lattice structure. For the memory chip 100 adopting the cross-lattice structure, the bit density of the memory chip 100 can be improved by stacking a plurality of memory cells 10. Furthermore, the two ends of the memory cell 10 are connected and led out through mutually crossed electrode wires.

[0041] like Figure 2As shown, the memory chip 100 includes a first memory cell 11 and a second memory cell 12 stacked along a first direction z. The first memory cell 11 includes a first bottom electrode 111, a first gating layer 112, a first intermediate electrode 113, a first phase change layer 114, and a first top electrode 115 stacked in sequence. The second memory cell 12 includes a second bottom electrode 121, a second gating layer 122, a second intermediate electrode 123, a second phase change layer 124, and a second top electrode 125 stacked in sequence. The second top electrode 125 is disposed close to the first bottom electrode 111.

[0042] The memory chip 100 further includes a first word line 141, a second word line 142, a first bit line 131, and a second bit line 132. In the first direction z, the first word line 141 and the second word line 142 are located between the first memory cell 11 and the second memory cell 12. The first word line 141 is connected to the first bottom electrode 111 of the first memory cell 11, the first bit line 131 is located at a side of the first memory cell 11 away from the first word line 141 and is connected to the first top electrode 115 of the first memory cell 11. The second word line 142 is connected to the second top electrode 125 of the second memory cell 12, the second bit line 132 is located at a side of the second memory cell 12 away from the second word line 142 and is connected to the second bottom electrode 121 of the second memory cell 12. The first word line 141 and the second word line 142 both extend along the second direction x. The first bit line 131 and the second bit line 132 both extend along the third direction y. The first direction z, the second direction x, and the third direction y intersect with each other.

[0043] The first bottom electrode 111, the first intermediate electrode 113, the first top electrode 115, the second bottom electrode 121, the second intermediate electrode 123, and the second top electrode 125 may include at least one of amorphous carbon (aC), carbon nanotubes, graphene, and tungsten. In a specific embodiment, the first bottom electrode 111, the first intermediate electrode 113, the first top electrode 115, the second bottom electrode 121, the second intermediate electrode 123, and the second top electrode 125 may include amorphous carbon. In another specific embodiment, at least one of the first bottom electrode 111, the first intermediate electrode 113, the first top electrode 115, the second bottom electrode 121, the second intermediate electrode 123, and the second top electrode 125 may include tungsten.

[0044] The first gate layer 112 and the second gate layer 122 may include a chalcogenide material, such as Zn x Te y ,Ge x Te y , Nb x O y or Si x As y Te zwait.

[0045] The first word line 141 , the second word line 142 , the first bit line 131 and the second bit line 132 include a conductive material, including but not limited to tungsten (W), cobalt (Co), copper (Cu), aluminum (Al), polysilicon, doped silicon, silicide, or any combination thereof.

[0046] Figure 3 Schematic diagram of the structure of the memory chip of some other embodiments provided by the present application. Figure 3 As shown, the memory chip 100 adopts a small-size electrode contact structure, and the electrode on at least one side of the phase change layer adopts a small-size contact structure (eg, a columnar contact structure) to achieve the size definition of the memory cell 10 .

[0047] like Figure 3 As shown, the memory chip 100 includes a substrate layer 21, a dielectric layer 22, a first electrode 23, a second electrode 24 and a phase change layer 25. The first electrode 23, the second electrode 24 and the phase change layer 25 constitute a memory cell 10. The dielectric layer 22 is disposed on the substrate layer 21. The first electrode 23 is buried in the dielectric layer 22. The first electrode 23 includes a columnar contact portion 231 and an extraction portion 232, and the columnar contact portion 231 and the extraction portion 232 are bent relative to each other and connected. The phase change layer 25 is in a layered shape. The phase change layer 25 is disposed on a side of the dielectric layer 22 away from the substrate layer 21 and is in contact with the columnar contact portion 231, and the portion where the columnar contact portion 231 contacts the phase change layer 25 defines a phase change region. The second electrode 24 is in a layered shape. The second electrode 24 is disposed on a surface of the phase change layer 25 away from the substrate layer 21. By applying a voltage V to the second electrode 24 and the extraction portion 232 of the first electrode 23, the phase change layer 25 can be controlled to undergo a phase transition.

[0048] The substrate layer 21 may include semiconductor materials such as silicon or germanium. The dielectric layer 22 may include insulating materials such as silicon oxide, silicon nitride or silicon oxynitride. The first electrode 23 and the second electrode 24 may include at least one of a variety of conductive materials such as copper, tungsten, titanium nitride, tantalum nitride, tungsten nitride, tungsten carbide and doped Si.

[0049] Figure 4 This is a schematic diagram of the structure of the memory chip of some other embodiments provided by the present application. Figure 4 As shown, the memory chip 100 may adopt a sinker contact structure, and a portion of the phase change layer 25 is located in a small-sized sinker hole, thereby achieving the definition of the size of the memory cell 10 .

[0050] like Figure 4 As shown, Figure 4 The structure of the memory chip 100 is similar to Figure 3The structure of the memory chip 100 shown is basically similar, and the similarities are not repeated. The differences include that the dielectric layer 22 includes a sink hole 221. The sink hole 221 is sunken from the surface of the dielectric layer 22 away from the substrate layer 21 to the surface of the dielectric layer 22 close to the substrate layer 21. The sink hole 221 exposes the columnar contact portion 231 of the first electrode 23. A portion of the phase change layer 25 is located in the sink hole 221. The area where the portion of the phase change layer 25 located in the sink hole 221 contacts the columnar contact portion 231 defines a phase change region.

[0051] From this we can see that Figures 2 to 4 The memory cell 10 of the memory chip 100 may adopt different structural designs. However, the memory cell 10 includes a phase change layer and two electrodes respectively located on both sides of the phase change layer.

[0052] Figures 2 to 4 The phase change layers in the memory 300 all include phase change materials. The phase change material, as the storage medium of the memory 300, directly affects the performance of the memory 300. For example, the crystallization speed, crystallization temperature, amorphous phase stability, thermal stability, storage window, cycle characteristics of the phase change material, and the adhesion between the phase change material and the electrode will affect the performance of the memory chip 100 and the memory 300.

[0053] In the present application, the phase change material includes a base material, Hf (hafnium) element and In (indium element).

[0054] The matrix material includes at least one element of Ge, Sb and Te, which can improve the crystallization speed of the phase change material and ensure that the memory 300 has a faster write (SET) speed.

[0055] The Hf element can inhibit the two-stage crystallization phenomenon of the base material during the crystallization process, further improve the crystallization speed of the phase change material, and further improve the writing speed of the memory 300 including the phase change material. In addition, the Hf element can increase the crystallization temperature of the phase change material, improve the thermal stability of the phase change material in the amorphous state, and then improve the high-temperature reliability of the memory 300, thereby improving the data retention of the device. In addition, the Hf element doped base material can improve the cycle characteristics of the memory and the adhesion between the phase change storage material and the electrode.

[0056] In element doping of the matrix material can improve the memory window, cycle characteristics and adhesion between the phase change memory material and the electrode.

[0057] The percentage of the number of atoms of the Hf element in the phase change material is greater than 0 and less than or equal to 20%. The percentage of the number of atoms of the In element in the phase change material is greater than 0 and less than or equal to 20%. In this way, a certain proportion of the Hf element and a certain proportion of the In element are doped into the matrix material at the same time to jointly strengthen the atomic bonding strength in the phase change material, improve the structural stability of the phase change material, and make the adhesion of the phase change material meet the requirements of semiconductor production. The risk of peeling between the phase change layer composed of the phase change material and the electrode is reduced, and the performance stability of the memory chip and the memory is improved. In addition, the Hf element and the In element cooperate with each other to dope the matrix material at the same time, which can inhibit the element segregation caused by the material in the matrix material under the action of the electric field and thermal effects, thereby improving the cycle durability and storage window of the memory chip and the memory between the writing process and the erasing (Reset) process.

[0058] It should be noted that the cycle durability is the maximum number of cycles for the phase change material to undergo a reversible phase change between the amorphous state (the phase change material is in a high resistance state) and the crystalline state (the phase change material is in a low resistance state), that is, the durability life. The greater the maximum number of cycles, the better the cycle durability. The storage window is the ratio of the resistance value of the phase change material in the amorphous state (Reset resistance) to the resistance value of the phase change material in the crystalline state (SET resistance). The larger the storage window, the larger the switching ratio of the memory 300.

[0059] Optionally, in the phase change material, the atomic number percentage of the Hf element may be greater than or equal to 0.1% and less than or equal to 18%. Optionally, in the phase change material, the atomic number percentage of the Hf element may be greater than or equal to 1% and less than or equal to 15%. Optionally, in the phase change material, the atomic number percentage of the Hf element may be greater than or equal to 2% and less than or equal to 12%. Optionally, in the phase change material, the atomic number percentage of the Hf element may be greater than or equal to 5% and less than or equal to 10%. Optionally, in the phase change material, the atomic number percentage of the Hf element may be greater than or equal to 7% and less than or equal to 9%. Optionally, in the phase change material, the atomic number percentage of the Hf element may be greater than or equal to 0.01% and less than or equal to 10%. Optionally, in the phase change material, the atomic number percentage of the Hf element may be greater than or equal to 0.1% and less than or equal to 8%. Optionally, in the phase change material, the atomic number percentage of the Hf element may be greater than or equal to 1% and less than or equal to 5%. Optionally, in the phase change material, the atomic number percentage of the Hf element may be greater than or equal to 8% and less than or equal to 20%. Optionally, in the phase change material, the atomic number percentage of the Hf element may be greater than or equal to 12% and less than or equal to 18%.

[0060] For example, in the phase change material, the atomic percentage of the Hf element can be 0.02%, 0.05%, 0.08%, 0.1%, 0.2%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.8%, 3.0%, 3.2%, 3.5%, 3.8%, 4.0%, 4.2%, 4.5%, 4.8%, 5.0%, 5.2%, 5.5%, 5.8%, 6.0%, 6.2%, 6.5%, 6.8%, 7.0%, 7.2%, 7.5%, 7.8%, 8.0%, 8.2%, 8.5%, 8.8%, 9.0%, 9.2%, 9.5%, 9.8 %, 10.0%, 10.2%, 10.5%, 10.8%, 11.0%, 11.2%, 11.5%, 11.8%, 12.0%, 12.2%, 12.5%, 12.8%, 13.0%, 13.2%, 13.5%, 13.8%, 14.0%, 14.2%, 14.5%, 14.8%, 15.0%, 15.2%, 15.5%, 15.8%, 16.0%, 16.2%, 16.5%, 16.8%, 17.0%, 17.2%, 17.5%, 17.8%, 18.0%, 18.2%, 18.5%, 18.8%, 19.0%, 19.2%, 19.5% or 19.8%.

[0061] Optionally, in the phase change material, the atomic number percentage of the In element may be greater than or equal to 1% and less than or equal to 18%. Optionally, in the phase change material, the atomic number percentage of the In element may be greater than or equal to 1.5% and less than or equal to 17%. Optionally, in the phase change material, the atomic number percentage of the In element may be greater than or equal to 3% and less than or equal to 15%. Optionally, in the phase change material, the atomic number percentage of the In element may be greater than or equal to 4% and less than or equal to 14%. Optionally, in the phase change material, the atomic number percentage of the In element may be greater than or equal to 5% and less than or equal to 10%. Optionally, in the phase change material, the atomic number percentage of the In element may be greater than or equal to 7% and less than or equal to 9%. Optionally, in the phase change material, the atomic number percentage of the In element may be greater than or equal to 0.01% and less than or equal to 15%. Optionally, in the phase change material, the atomic number percentage of the In element may be greater than or equal to 0.1% and less than or equal to 13%. Optionally, in the phase change material, the atomic number percentage of the In element may be greater than or equal to 1% and less than or equal to 8%. Optionally, in the phase change material, the atomic number percentage of the In element may be greater than or equal to 2% and less than or equal to 10%. Optionally, in the phase change material, the atomic number percentage of the In element may be greater than or equal to 8% and less than or equal to 15%.

[0062] For example, in the phase change material, the atomic percentage of In element can be 0.02%, 0.05%, 0.08%, 0.1%, 0.2%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.8%, 3.0%, 3.2%, 3.5%, 3.8%, 4.0%, 4.2%, 4.5%, 4.8%, 5.0%, 5.2%, 5.5%, 5.8%, 6.0%, 6.2%, 6.5%, 6.8%, 7.0%, 7.2%, 7.5%, 7.8%, 8.0%, 8.2%, 8.5%, 8.8%, 9.0%, 9.2%, 9.5%, 9.8 %, 10.0%, 10.2%, 10.5%, 10.8%, 11.0%, 11.2%, 11.5%, 11.8%, 12.0%, 12.2%, 12.5%, 12.8%, 13.0%, 13.2%, 13.5%, 13.8%, 14.0%, 14.2%, 14.5%, 14.8%, 15.0%, 15.2%, 15.5%, 15.8%, 16.0%, 16.2%, 16.5%, 16.8%, 17.0%, 17.2%, 17.5%, 17.8%, 18.0%, 18.2%, 18.5%, 18.8%, 19.0%, 19.2%, 19.5% or 19.8%.

[0063] In some embodiments, in the phase change material, the atomic percentage of the In element in the phase change material is greater than the atomic percentage of the Hf element in the phase change material, so as to improve the storage window of the memory while taking into account the cycle durability of the memory.

[0064] In some embodiments, the phase change material further includes an A element, and the A element is selected from at least one of C, N, O and Si, and the atomic number percentage of the A element in the phase change material is greater than 0% and less than or equal to 20%. In this way, the Hf element, In and the A element co-doped with the matrix material can simultaneously improve the operating speed, cycle durability and storage window of the memory 300, reduce the risk of peeling between the phase change layer and the electrode, improve the performance reliability and data retention of the memory 300, and facilitate the large-scale production of the memory 300 including the phase change material. In addition, the Hf element, In and the A element co-doped with the matrix material can flexibly and controllably adjust the composition, and it is easy to achieve. At the same time, it reduces production risks and expands the range of choices for phase change materials that can be used for large-scale production.

[0065] It should be noted that the A element can inhibit the phase separation phenomenon of the matrix material during the crystallization process, refine the grain size of the phase change material during the crystallization process, and improve the problem of forming large-sized grains during the crystallization process, thereby improving the cycle durability and storage window of the memory 300 between the writing process and the erasing (Reset) process. In addition, the A element and the constituent elements of the matrix material have strong bonding capabilities. The addition of the A element can strengthen the bonding strength of the phase change material and improve the adhesion between the phase change material and the electrode, thereby improving the strength of the phase change material and further reducing the risk of peeling between the phase change layer and the electrode. In addition, the addition of the A element can also improve the consistency of small-size devices and achieve an increase in the yield of the memory 300.

[0066] In some embodiments, the A element includes at least one of N and O. Optionally, the A element includes O. Optionally, the A element includes N. Optionally, the A element includes N and O. In this way, since the N and O elements are easy to dope and control in the semiconductor process, the N and O elements have better process compatibility and less side effects, which is conducive to promoting the application of phase change materials in phase change storage.

[0067] Optionally, in the phase change material, the atomic number percentage of element A may be greater than or equal to 0.1% and less than or equal to 18%. Optionally, in the phase change material, the atomic number percentage of element A may be greater than or equal to 1% and less than or equal to 17%. Optionally, in the phase change material, the atomic number percentage of element A may be greater than or equal to 1.5% and less than or equal to 15%. Optionally, in the phase change material, the atomic number percentage of element A may be greater than or equal to 4% and less than or equal to 12%. Optionally, in the phase change material, the atomic number percentage of element A may be greater than or equal to 5% and less than or equal to 10%. Optionally, in the phase change material, the atomic number percentage of element A may be greater than or equal to 7% and less than or equal to 9%. Optionally, in the phase change material, the atomic number percentage of element A may be greater than or equal to 1% and less than or equal to 10%. Optionally, in the phase change material, the atomic number percentage of element A may be greater than or equal to 1.5% and less than or equal to 8%. Optionally, in the phase change material, the atomic number percentage of element A may be greater than or equal to 1% and less than or equal to 4%. Optionally, in the phase change material, the atomic number percentage of element A may be greater than or equal to 10% and less than or equal to 20%. Optionally, in the phase change material, the atomic number percentage of element A may be greater than or equal to 13% and less than or equal to 18%.

[0068] For example, in the phase change material, the atomic percentage of element A can be 0.02%, 0.05%, 0.08%, 0.1%, 0.2%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.8%, 3.0%, 3.2%, 3.5%, 3.8%, 4.0%, 4.2%, 4.5%, 4.8%, 5.0%, 5.2%, 5.5%, 5.8%, 6.0%, 6.2%, 6.5%, 6.8%, 7.0%, 7.2%, 7.5%, 7.8%, 8.0%, 8.2%, 8.5%, 8.8%, 9.0%, 9.2%, 9.5%, 9.8 %, 10.0%, 10.2%, 10.5%, 10.8%, 11.0%, 11.2%, 11.5%, 11.8%, 12.0%, 12.2%, 12.5%, 12.8%, 13.0%, 13.2%, 13.5%, 13.8%, 14.0%, 14.2%, 14.5%, 14.8%, 15.0%, 15.2%, 15.5%, 15.8%, 16.0%, 16.2%, 16.5%, 16.8%, 17.0%, 17.2%, 17.5%, 17.8%, 18.0%, 18.2%, 18.5%, 18.8%, 19.0%, 19.2%, 19.5% or 19.8%.

[0069] In some embodiments, in the phase change material, the atomic percentage of the In element in the phase change material is greater than the atomic percentage of the A element in the phase change material, so as to better improve the storage window of the memory.

[0070] In some embodiments, when the A element includes the N element, in the phase change material, the atomic number percentage of the Hf element is greater than or equal to 0.1% and less than or equal to 10%, the atomic number percentage of the N element is greater than or equal to 0.1% and less than or equal to 10%, and the atomic number percentage of the In element is greater than 0% and less than or equal to 20%. In this way, the adhesion between the phase change material and the electrode is significantly improved, the storage window and cycle durability of the memory are improved, and the process difficulty is reduced.

[0071] In some embodiments, when the A element includes the O element, in the phase change material, the atomic number percentage of the Hf element is greater than or equal to 0.1% and less than or equal to 10%, the atomic number percentage of the O element is greater than or equal to 0.1% and less than or equal to 10%, and the atomic number percentage of the In element is greater than 0% and less than or equal to 20%. In this way, the adhesion between the phase change material and the electrode is significantly improved, the storage window and cycle durability of the memory are improved, and the process difficulty is reduced.

[0072] In some embodiments, the matrix material includes Ge, Sb and Te. In the phase change material, the atomic percentage of Ge is greater than or equal to 0 and less than or equal to 50%, the atomic percentage of Sb is greater than or equal to 10% and less than or equal to 50%, and the atomic percentage of Te is greater than or equal to 35% and less than or equal to 70%. In this way, the crystallization speed of the phase change material can be further improved, ensuring that the memory 300 has a faster write (SET) speed.

[0073] Optionally, in the phase change material, the percentage of the number of atoms of the Ge element is greater than or equal to 2% and less than or equal to 45%. Optionally, in the phase change material, the percentage of the number of atoms of the Ge element is greater than or equal to 5% and less than or equal to 40%. Optionally, in the phase change material, the percentage of the number of atoms of the Ge element is greater than or equal to 8% and less than or equal to 35%. Optionally, in the phase change material, the percentage of the number of atoms of the Ge element is greater than or equal to 10% and less than or equal to 25%.

[0074] Optionally, in the phase change material, the atomic number percentage of the Sb element is greater than or equal to 12% and less than or equal to 45%. Optionally, in the phase change material, the atomic number percentage of the Sb element is greater than or equal to 15% and less than or equal to 40%. Optionally, in the phase change material, the atomic number percentage of the Sb element is greater than or equal to 18% and less than or equal to 35%. Optionally, in the phase change material, the atomic number percentage of the Sb element is greater than or equal to 20% and less than or equal to 33%.

[0075] Optionally, in the phase change material, the atomic percentage of Te element is greater than or equal to 40% and less than or equal to 65%. Optionally, in the phase change material, the atomic percentage of Te element is greater than or equal to 55% and less than or equal to 60%.

[0076] In some embodiments, when the A element is the N element, the chemical formula of the phase change material is (N) x1 (Hf) y1 (In) z1 (Ge m1 Sb n1 Te k1 ) 1-x1-y1-z1. Among them, x1 represents the atomic number percentage of N element, y1 represents the atomic number percentage of Hf element, z1 represents the atomic number percentage of In element, m1 / n1 / k1 represents the atomic number ratio of Ge, Sb and Te, m1+n1+k1=100%; 0.1%≤x1≤10%, 0.1%≤y1≤10%, 0.1%≤z1≤20%, 0%≤m1≤50%, 10%≤n1≤50%, 35%≤k1≤70%. In this way, the adhesion between the phase change material and the electrode can be significantly improved, the storage window of the memory can be expanded, and the cycle durability of the memory can be improved.

[0077] Optionally, 1%≤x1≤8%, 1%≤y1≤8%, 1%≤z1≤18%, 10%≤m1≤40%, 15%≤n1≤50%, 40%≤k1≤70%, 70%≤1-x1-y1-z1≤98%. In this way, the adhesion between the phase change material and the electrode can be significantly improved, the storage window of the memory can be expanded, and the cycle durability of the memory can be improved.

[0078] Optionally, 1%≤x1≤5%, 1%≤y1≤5%, 1%≤z1≤15%, 10%≤m1≤30%, 15%≤n1≤50%, 45%≤k1≤75%, and 73%≤1-x1-y1-z1≤95%.

[0079] In some embodiments, the phase change material includes (Ge 12.5 Sb 37.5 Te 50 ) 90 Hf5N4In1、(Ge 12.5 Sb 37.5 Te 50 ) 81 Hf5N4In 10 and (Ge 12.5 Sb 37.5 Te 50 ) 73 Hf5N4In 18 In this way, the adhesion between the phase change material and the electrode can be significantly improved, the storage window of the memory can be expanded, and the cycle durability of the memory can be improved.

[0080] In some embodiments, when the A element is the O element, the chemical formula of the phase change material is (O) x2 (Hf) y2 (In) z2 (Ge m2 Sb n2 Te k2 ) 1-x2-y2-z2. Among them, x2 represents the atomic percentage of O element, y2 represents the atomic percentage of Hf element, z2 represents the atomic percentage of In element, m2 / n2 / k2 represents the atomic ratio of Ge, Sb and Te, m2+n2+k2=100%; 0.1%≤x2≤10%, 0.1%≤y2≤10%, 0.1%≤z2≤20%, 0%≤m2≤50%, 10%≤n2≤50%, 35%≤k2≤70%. In this way, the adhesion between the phase change material and the electrode can be significantly improved, the storage window of the memory can be expanded, and the cycle durability of the memory can be improved.

[0081] Optionally, 1%≤x2≤8%, 1%≤y2≤8%, 1%≤z2≤18%, 0%≤m2≤50%, 10%≤n2≤50%, 35%≤k2≤70%, 70%≤1-x2-y2-z2≤98%. In this way, the adhesion between the phase change material and the electrode can be significantly improved, the storage window of the memory can be expanded, and the cycle durability of the memory can be improved.

[0082] In some embodiments, the adhesion between the electrode and the phase change layer is characterized by an energy release rate, and the energy release rate is greater than or equal to 0.9 J / m 2 In this way, the risk of peeling between the phase change layer and the electrode is reduced. Optionally, the energy release rate is greater than or equal to 1.0 J / m 2 .

[0083] The electrode includes at least one of a metal material and a non-metal material. The metal material includes at least one of tungsten (W), tungsten nitride (WN), titanium (Ti), titanium nitride (TiN) and WSiN. The non-metal material includes at least one of carbon, nitrogen, oxygen and silicon. Optionally, the electrode includes tungsten. In this way, the electrode has better adhesion with the phase change material, further reducing the risk of peeling between the electrode and the phase change material.

[0084] It can be seen from this that the selection of constituent elements and the selection of the content of constituent elements of the phase change material of the present application can improve the operating speed, cycle durability and storage window of the memory 300, reduce the risk of peeling between the phase change layer including the phase change material and the electrode and thus reduce production risks, and can also improve the performance reliability, data retention, process compatibility and process yield of the memory 300, which is conducive to the large-scale production of the memory 300 including the phase change material.

[0085] The present application also provides a method for preparing the above phase change material, the preparation method comprising the following steps:

[0086] Providing a first target, a second target, and a third target, wherein the first target includes at least one element of Ge, Sb, and Te, the second target includes Hf, and the third target includes In; and

[0087] The phase change material is formed by at least a first target, a second target and a third target.

[0088] In some embodiments, forming a phase change material using the first target material, the second target material, and the third target material includes: forming the phase change material using a deposition process or a growth process. The deposition process includes but is not limited to chemical vapor deposition (CVD), physical vapor deposition (PVD), plasma enhanced chemical vapor deposition (PECVD), sputtering, metal organic chemical vapor deposition (MOCVD), or atomic layer deposition (ALD).

[0089] In some embodiments, the preparation method further includes: providing a fourth target material;

[0090] Forming the phase change material using at least a first target material, a second target material, and a third target material includes:

[0091] The phase change material is formed by using a first target, a second target, a third target and a fourth target.

[0092] It is understandable that the phase change material may be formed using a single target material including at least one element among Ge, Sb and Te, Hf and In.

[0093] The performance of the above phase change material is verified in combination with the embodiments and comparative examples below.

[0094] Adhesion test

[0095] The adhesion test method includes the following steps:

[0096] A first carbon layer (C1, with a thickness greater than or equal to 20 nanometers), a first tungsten electrode layer (W1, with a thickness greater than or equal to 3 nanometers), a phase change layer (PCM, with a thickness greater than or equal to 40 nanometers), a second tungsten electrode layer (W2, with a thickness greater than or equal to 3 nanometers) and a second carbon layer (C2, with a thickness greater than or equal to 20 nanometers) are sequentially formed on a first silicon substrate, and a second silicon substrate identical to the first silicon substrate is bonded to the second carbon layer (C2) by an epoxy resin adhesive to obtain a test sample;

[0097] The test sample is stretched frontally to apply tension to the first silicon substrate and the second silicon substrate until the first silicon substrate and the second silicon substrate are separated, and the energy release rate required for separation is recorded.

[0098] Table 1 Composition and energy release rate of phase change materials of Examples 1 to 3 and Comparative Examples 1 to 2

[0099]

[0100] Combined with Table 1, it can be seen that the energy release rate corresponding to Examples 1 to 3 is greater than or equal to 0.95 J / m 2 , which is significantly greater than the energy release rates corresponding to Comparative Examples 1 and 2. Therefore, the Hf element, N element, and In element doping the matrix material including Ge, Sb, and Te at the same time can better improve the adhesion between the phase change material and the tungsten electrode.

[0101] Operation speed and storage window

[0102] Table 2 Composition of phase change materials of Examples 1 to 3 and Comparative Examples 1 and 3

[0103] Composition of phase change materials Example 1 <![CDATA[(Ge 12.5 Sat 37.5 You 50 ) 90 Hf5N4In1]]> Example 2 <h2 style=";text-align:left;direction:ltr"><![CDATA[(Ge <h2 style=";text-align:left;direction:ltr"> 12.5 <h2 style=";text-align:left;direction:ltr"> Sb<h2 style=";text-align:left;direction:ltr"> 37.5 <h2 style=";text-align:left;direction:ltr"> Te<h2 style=";text-align:left;direction:ltr"> 50 <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> 81 <h2 style=";text-align:left;direction:ltr"> Hf5N4In<h2 style=";text-align:left;direction:ltr"> 10 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> Example 3 <h2 style=";text-align:left;direction:ltr"><![CDATA[(Ge <h2 style=";text-align:left;direction:ltr"> 12.5 <h2 style=";text-align:left;direction:ltr"> Sb<h2 style=";text-align:left;direction:ltr"> 37.5 <h2 style=";text-align:left;direction:ltr"> Te<h2 style=";text-align:left;direction:ltr"> 50 <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> 73 <h2 style=";text-align:left;direction:ltr"> Hf5N4In<h2 style=";text-align:left;direction:ltr"> 18 <h2 style=";text-align:left;direction:ltr"><!-- 9 --> ]]><h2 style=";text-align:left;direction:ltr"> Comparative Example 1 <![CDATA[(Ge 12.5 Sb 37.5 Te 50 ) 91 Hf5N4]]> Comparative Example 3 <![CDATA[(Ge 12.5 Sb 37.5 The 50 ) 86 N4In 10 ]]>

[0104] Combining Table 2 and Figure 5 It can be seen that for Examples 1 to 3, Hf elements, N elements and In elements are simultaneously doped into a matrix material including Ge, Sb and Te, and the time for the erase operation and write operation of the memory can be 30ns, which improves the operation speed of the memory. Moreover, the doping ratio of Hf elements, N elements and In elements is within a certain range, and the storage window of the memory is large. In addition, the doping ratio of Hf elements, N elements and In elements is within a certain range, and the ratio of the resistance value corresponding to the erase operation to the resistance value corresponding to the write operation at different write operation times tends to be stable, which can improve the performance stability of the memory.

[0105] It should be noted that Figure 5The bar graph in R ratio represents the storage window of write pulses of different widths (times), and the higher the height of the bar graph, the larger the storage window. In Example 1, when the width of the write pulse is 15ns, the storage window is small, and the memory can still realize the storage function.

[0106] The description of the above embodiments is only used to help understand the technical solutions and core ideas of the present application. Ordinary technical personnel in this field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some of the technical features therein with equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A phase change material, characterized in that: The phase change material comprises: Base material; Hf element, the atomic number percentage of Hf element in the phase change material is greater than 0 and less than or equal to 20%; and In element, the atomic number percentage of In element in the phase change material is greater than 0 and less than or equal to 20%.

2. The phase change material according to claim 1, characterized in that: The atomic percentage of the Hf element in the phase change material is greater than or equal to 1% and less than or equal to 15%; The atomic number percentage of In element in the phase change material is greater than or equal to 1% and less than or equal to 18%.

3. The phase change material according to claim 1, characterized in that: The phase change material also includes: Element A, element A is at least one element selected from C, N, O and Si, and the atomic number percentage of element A in the phase change material is greater than 0% and less than or equal to 20%.

4. The phase change material according to claim 3, characterized in that: The atomic number percentage of the A element in the phase change material is greater than or equal to 1% and less than or equal to 10%.

5. The phase change material according to claim 3, characterized in that: In the phase change material, the atomic number percentage of the In element in the phase change material is greater than the atomic number percentage of the A element in the phase change material.

6. The phase change material according to any one of claims 1 to 5, characterized in that: The matrix material includes at least one element of Ge, Sb and Te.

7. The phase change material according to claim 6, characterized in that: The matrix material includes Ge, Sb and Te elements; In the phase change material, the atomic number percentage of Ge element is greater than or equal to 0% and less than or equal to 50%, the atomic number percentage of Sb element is greater than or equal to 10% and less than or equal to 50%, and the atomic number percentage of Te element is greater than or equal to 35% and less than or equal to 70%.

8. The phase change material according to claim 1, characterized in that: The general chemical formula of the phase change material is (N) x1 (Hf) y1 (In) z1 (Ge m1 Sb n1 Te k1 ) 1-x1-y1-z1 ; Among them, x1 represents the atomic number percentage of N element, y1 represents the atomic number percentage of Hf element, z1 represents the atomic number percentage of In element, and m1 / n1 / k1 represents the atomic number ratio of Ge, Sb and Te; 0.1%≤x1≤10%, 0.1%≤y1≤10%, 0.1%≤z1≤20%, 0%≤m1≤50%, 10%≤n1≤50%, 35%≤k1≤70%.

9. The phase change material according to claim 8, characterized in that: The phase change material includes (Ge 12.5 Sb 37.5 Te 50 ) 90 Hf5N4In1、(Ge 12.5 Sb 37.5 Te 50 ) 81 Hf5N4In 10 and (Ge 12.5 Sb 37.5 Te 50 ) 73 Hf5N4In 18 At least one of .

10. A phase change memory, characterized in that: The memory comprises the phase change material according to any one of claims 1-9.